2020
DOI: 10.1093/mnras/staa2045
|View full text |Cite
|
Sign up to set email alerts
|

SNR G39.2−0.3, an hadronic cosmic rays accelerator

Abstract: Recent results obtained with gamma-ray satellites have established supernova remnants as accelerators of GeV hadronic cosmic rays. In such processes, CRs accelerated in SNR shocks interact with particles from gas clouds in their surrounding. In particular, the rich medium in which core-collapse SNRs explode provides a large target density to boost hadronic gamma-rays. SNR G39.2–0.3 is one of the brightest SNR in infrared wavelengths, and its broad multi-wavelength coverage allows a detailed modeling of its rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The 22 Ne/ 20 Ne ratio observed in CRs is for instance a factor of 5 higher than in the solar wind [500], pointing to a sizeable contribution of CRs being accelerated from win-material of massive stars. At the same time, is the acceleration of heavier nuclei from the material surrounding massive stars affecting the gamma-ray signal that has to be expected at the hadronic low-energy cutoff [501,502]. The precise measurements of nuclei-ratios [503] reveal features in the abundance-ratios that either point to necessary modification of our models for the Galactic CR propagation or at particularities of the acceleration-process itself.…”
Section: Supernova Remnantsmentioning
confidence: 98%
“…The 22 Ne/ 20 Ne ratio observed in CRs is for instance a factor of 5 higher than in the solar wind [500], pointing to a sizeable contribution of CRs being accelerated from win-material of massive stars. At the same time, is the acceleration of heavier nuclei from the material surrounding massive stars affecting the gamma-ray signal that has to be expected at the hadronic low-energy cutoff [501,502]. The precise measurements of nuclei-ratios [503] reveal features in the abundance-ratios that either point to necessary modification of our models for the Galactic CR propagation or at particularities of the acceleration-process itself.…”
Section: Supernova Remnantsmentioning
confidence: 98%
“…Spectral measurements of gamma-ray emission from for example IC443 (Acciari et al 2009), Cas A (Abdo et al 2010), SN 1006 (Acero et al 2010), the Tycho SNR (Acciari et al 2011), and W44 (Malkov et al 2011;Cardillo et al 2014) indicate a considerable softening compared to the expected power-law index s = 2, which may be modelled in different ways. For example, diffusive re-acceleration of Galactic CRs has been proposed to explain the spectral shape of W44 (Cardillo et al 2016), but was found implausible in other studies on account of the large thickness of radiative shocks and the paucity of Galactic CRs to be re-accelerated (Brose et al 2020;de Oña Wilhelmi et al 2020). Other options include re-acceleration in fast-mode turbulence downstream of the forward shock (FS, Pohl et al 2015;Wilhelm et al 2020), fast motion of downstream turbulence (Caprioli et al 2020), and inefficient particle confinement in the vicinity of the SNR caused by the attenuation or weak driving of Alfvén waves (Malkov et al 2011;Celli et al 2019;Brose et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral measurements of gammaray emission from, e.g., IC443 (Acciari et al 2009), Cas A (Abdo et al 2010), SN 1006 (Acero et al 2010), Tycho's SNR (Acciari et al 2011), and W44 (Malkov et al 2011;Cardillo et al 2014) indicate a considerable softening compared to the expected power-law index s = 2, which may be modelled in different ways. For example, diffusive reacceleration of galactic CRs has been proposed to explain the spectral shape of W44 (Cardillo et al 2016), but was found implausible in other studies on account of the large thickness of radiative shocks and the paucity of Galactic cosmic rays to be re-accelerated (Brose et al 2020;de Oña Wilhelmi et al 2020). Other options include re-acceleration in fast-mode turbulence downstream of the forward shock (Pohl et al 2015;Wilhelm et al 2020), fast motion of downstream turbulence (Caprioli et al 2020), and inefficient particle confinement in the vicinity of the SNR caused by the attenuation or weak driving of Alfvén waves (Malkov et al 2011;Celli et al 2019;Brose et al 2020).…”
Section: Introductionmentioning
confidence: 99%